If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 3) = 12 Reorder the terms: 3(3 + 2x) = 12 (3 * 3 + 2x * 3) = 12 (9 + 6x) = 12 Solving 9 + 6x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 6x = 12 + -9 Combine like terms: 9 + -9 = 0 0 + 6x = 12 + -9 6x = 12 + -9 Combine like terms: 12 + -9 = 3 6x = 3 Divide each side by '6'. x = 0.5 Simplifying x = 0.5
| 5x=x^2-50 | | -120+9y+80=41 | | 15n^2-80n+25=0 | | -120+9y+8c=41 | | 40=2(y-5) | | 14=y+8+y | | 4x+14=114-4 | | 10x-23=6+1 | | 2y+6-1=19 | | 9k^2+12k+4=0 | | 2(y+4)=16 | | 64x^4-80x^2y+25y^2= | | 12-2g=6 | | 102.8=g+-66.09 | | 10+9=8x+23 | | 25n^2+10n+1=0 | | 4x^2-9x+17=7x+2 | | 6ln(3x)=8 | | y+10+2y=25 | | f=0.5*x^2-1.5*x-0.375 | | 5a+3=12+2a | | 4(x+1)=16 | | =0.5*x^2-1.5*x-0.375 | | 3x+(-x)= | | 20x+75=30x+50 | | 3(y+2)=12 | | 2a-4=18-9a | | 102.8=g+66.09 | | y=-16t^2+18t+10 | | k^2+13k+30=0 | | 9a^2+4a^2-8a^3= | | x^2-14x+3=-9x-3 |